PERANAN DINAS SOSIAL DALAM MEMBERIKAN PEMBINAAN TERHADAP ANAK JALANAN DI KOTA MEDAN - Rita Vinolia Aruan; Roy Frendrick Halawa (Jurnal Darma Agung, 2019)
This research is a descriptive qualitative research. In this research the technique of data sampling is purposive sampling technique. The data collected by the instrument of observation, interview, and documentation. There are two types of data in this research, primary data and secondary data. The research is conducted in the office of social department of Medan City which is located at Jl. Pinang Baris, district Sunggal of Medan, Medan City, North Sumatera. The result of this research described that the role of Social Department is very important in case of giving counseling to the street children in Medan city which is in the form of (1) giving skill training such as making florist board, tissue box, and making cloth painting, and (2) giving Moral guidance. There are some obstacles such as the lack of structure and infra structure especially in house of their living, budget which is still very low in this program of counseling, guiding, and training the street children.